Pengaruh Model Pembelajaran Kooperatif Tipe Round Robin Brainstorming terhadap Kemampuan Mengulas Karya Fiksi Kelas VIIISMPN 17 Batanghari - Pebriyanti, Melly; Rustam, Rustam; Rasdawita, Rasdawita (Jurnal Ilmiah Dikdaya, 2024)
This research aims to determine the significant influence of implementing the Round Robin Brainstorming (RRB) typecooperative learning model on the ability to review fiction works of class VIII studentsat SMPN 17 Batanghari. This research usesa quantitative approach with a Quasi Experimental design. Two groups were used in this research: an experimental group and acontrol group, with a Pretest-Posttest Control Group Design. The research results show that the application of the RRB typecooperative learning model has asignificant influence on increasing students' ability to review works of fiction. This is proven bythe average scorefor the experimental class which reached 81.41, while the control class only reached 73.43. Thus, the RRB typecooperative learning model has proven to be effective in improving the ability to review works of fiction of class VIII students atSMPN 17 Batanghari.